ESTABLISHMENT OF PROJECT MANAGEMENT AND INNOVATION POTENTIAL OF ENTERPRISES - Олександра Ковальчук; Юлія Гутарева; Дар’я Жовта (Економіка та суспільство, 2022)
Since the end of the 1980s, the role taken by differentiation strategies in Western economies has been at the origin of significant changes in the organization of the design of new companies' products. These developments have given rise to an essential current of research which has highlighted the importance of the project management method in the performance of firms' design. The organization by project appears as the privileged organizational form in developing innovative products, services or processes. When approaching such a subject, the first difficulty to be resolved is the polysemy of the terms used, the words «projects» and «innovation» used today to describe very diverse realities. The historical markets of companies are increasingly saturated and push them towards high-growth countries, for which they innovate somewhat different from what they practice in their country of origin.